Improving Care of STEMI in the United States 2008 to 2012: A Report From the American Heart Association Mission: Lifeline Program. Issue 1 (8th January 2019) - Granger, Christopher B.; Bates, Eric R.; Jollis, James G.; Antman, Elliott M.; Nichol, Graham; O'Connor, Robert E.; Gregory, Tammy; Roettig, Mayme L.; Peng, S. Andrew; Ellrodt, Gray; Henry, Timothy D.; French, William J.; et al.
Abstract : Background: We aimed to determine the change in treatment strategies and times to treatment over the first 5 years of the Mission: Lifeline program. Methods and Results: We assessed pre‐ and in‐hospital care and outcomes from 2008 to 2012 for patients with ST‐segment–elevation myocardial infarction at US hospitals, using data from the National Cardiovascular Data Registry Acute Coronary Treatment and Intervention Outcomes Network Registry—Get With The Guidelines Registry. In‐hospital adjusted mortality was calculated including and excluding cardiac arrest as a reason for primary percutaneous coronary intervention delay. A total of 147 466 patients from 485 hospitals were analyzed. There was a decrease in the proportion of eligible patients not treated with reperfusion (6.2% versus 3.3%) and treated with fibrinolytic therapy (13.4% versus 7.0%). Median time from symptom onset to first medical contact was unchanged (≈50 minutes). Use of prehospital ECGs increased (45% versus 71%). All major reperfusion times improved: median first medical contact‐to‐device for emergency medical systems transport to percutaneous coronary intervention–capable hospitals (93 to 84 minutes), first door‐to‐device for transfers for primary percutaneous coronary intervention (130 to 112 minutes), and door‐in–door‐out at non–percutaneous coronary intervention–capable hospitals (76 to 62 minutes) (all P <0.001 over 5 years). Rates of cardiogenic shock and cardiac arrest, and overall in‐hospital mortality increased (5.7% to 6.3%). Adjusted mortality excluding patients with known cardiac arrest decreased by 14% at 3 years and 25% at 5 years ( P <0.001). Conclusions: Quality of care for patients with ST‐segment–elevation myocardial infarction improved over time in Mission: Lifeline, including increased use of reperfusion therapy and faster times‐to‐treatment. In‐hospital mortality improved for patients without cardiac arrest but did not appear to improve overall as the number of these high‐risk patients increased.